The History of the Bornholm island in the Years 1940–1946. - Magda Gawinecka-Woźniak (Studia Maritima, 2013)
The article presents the history of the Bornholm Island in the years 1940–1946. WWII and a dozen or so months after it ended have constituted one of the most significant moments in this island’s history. This is because at this time its inhabitants experienced both the German occupation and the Soviet liberation and subsequent occupation. In the island the war lasted from April 10, 1940, i.e. from its occupation by German units, to April 5, 1946 when the last ship carrying Red Army soldiers aboard sailed away from Rønne. During the German occupation the development of events on the island differed significantly from the parallel experience of the rest of Denmark, for in Bornholm the German exerted the “mild” version of the occupation even though the place gradually became a German war theatre, too. The situation changed in May 1945, the time when Soviet bombs were cast on the island while the rest of Denmark celebrated the regaining of liberty. The article explains the motifs behind these actions to have been undertaken by the Soviet Union as well as the position of the Danish government towards this situation. The situation was the more surprising for, on the whole, the Danish never protested against the Soviet occupation of the island. The article ends in an explanation of the circumstances leading to the withdrawal of the Red Army from Bornholm.